Remittances and value added across economic sub-sectors in sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2021)
This research assesses the relevance of enhancing remittances on value added across economic sectors in sub-Saharan Africa for the period 1980 to 2014 using the Generalised Method of Moments. First, no significant net effects on added value to the agricultural sector are apparent. Second, enhancing remittances engenders a positive net effect on added value to the manufacturing sector. Third, there are negative net effects on added value to the service sector. Given that the unfavourable net incidence of remittances to the service sector is associated with a positive marginal or conditional effect, the analysis is extended by computing thresholds at which remittances induce net positive effects on added value to the service sector. The extended analysis shows that a remittance threshold of 48.5% of GDP is the critical mass needed for further enhancement of remittances to engender positive net effects on value added to the service sector.
Keywords: E23; F24; F30; O16; O55; 330; Economic Output; Remitances; Sub-Saharan Africa